2009
DOI: 10.1016/s0828-282x(09)70160-6
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Opportunities for improving end-of-life care for patients with advanced heart failure

Abstract: H eart failure (HF) is a complex and progressive condition associated with high morbidity and mortality rates, and considerable health resource use (1,2). Approximately 500,000 Canadians are living with HF and 50,000 new cases are diagnosed annually (3). Based on increases in the numbers of the aging population and improvements in the treatment of myocardial infarction, it is projected that the incidence of HF will double by 2025 (2). A recent analysis of 9943 patients in Ontario who were followed after an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 19 publications
(20 reference statements)
0
64
0
5
Order By: Relevance
“…Recent studies provide insights into patient and family member perspectives on communication about goals of care in advanced HF,3, 4, 11, 12 but comparatively little is known about the perspective of cardiology clinicians. Before designing and evaluating interventions to improve decision‐making about goals of care for patients with advanced HF, an understanding of clinicians' perceived barriers is needed so that interventions can be tailored to overcome these barriers 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies provide insights into patient and family member perspectives on communication about goals of care in advanced HF,3, 4, 11, 12 but comparatively little is known about the perspective of cardiology clinicians. Before designing and evaluating interventions to improve decision‐making about goals of care for patients with advanced HF, an understanding of clinicians' perceived barriers is needed so that interventions can be tailored to overcome these barriers 17.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided insights into the perspectives of seriously ill hospitalized patients with HF, and their families, and have identified that EOL communication and decision‐making are important to patients and families, but their needs related to these issues remain unmet 3, 4, 11, 12. Before developing tailored solutions to improve communication and decision‐making about goals of care for hospitalized patients with advanced HF, there is a need to also understand the barriers and facilitators to this process from clinicians' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the dyads stated the need to improve communication between the institutional and community levels. Some of the most frequent perceptions were: the lack of communication and interdisciplinary coordination or the use of hospital management systems as a shield to cover the inability or lack of will upon taking action, 21 the scarce implication of patients and relatives with community PC networks 26 , poor coordination in the continuity of care, 15,16,19,25 fragmentation in care out of the hospital, and scarce community support. 16 Additionally, honesty in communication was especially valued by the dyads; a concrete example is the importance of communicating in clear, delicate and simple manner about the proximity of death.…”
Section: Effective Communication Among Those Involved With Caringmentioning
confidence: 99%
“…15,[17][18][19][20][21][22]26 In relation to the need for contact with the PC team, several dyads stated not having someone to call in case of having doubts about the care for a loved one. 18,20 Some studies, on the contrary, showed quality telephone follow up of the dyads and even described the possibility of expanding access to professionals to 24 hours through information technology tools.…”
Section: Education For Caring For the Person At Homementioning
confidence: 99%
See 1 more Smart Citation